Failed TAVI in TAVI Implantation: TAVI Dislocation Followed by Ensuing Surgical Graft Resection - Róbert Novotný; Jaroslav Hlubocký; Tomáš Kovárník; Petr Mitáš; Zuzana Hlubocka; Jan Rulíšek; Sevim Ismihan Gulmez; Shubjiwan Kaur Ghotra; Jaroslav Lindner (Case Reports in Cardiology)
We are presenting a case report of failed valve-in-valve treatment of severe aortic stenosis. A control ultrasonography after TAVI implantation revealed a severe aortic regurgitation of the graft which was subsequently unresolved with postimplantation dilatation. Second TAVI was implanted with cranial dislocation to the aortic root. Patient underwent a CT examination to clarify the TAVI in TAVI position. Patient underwent a surgical resection of TAVI with implantation of biological aortic valve prosthesis. In situations where TAVI treatment fails or is complicated beyond the possibility of endovascular repair, surgical intervention despite its higher risks is the preferred choice.